Farhat Hashad’s efforts for Maghreb trade union unity 1946- 1952 - ziane, lakhdar (The Algerian Historical Journal, 2026)
This study aims to understand the nature of the project for the unity of the Arab Maghreb from the trade union angle which had been advocated by the Tunisian activist and trade unionist Farhat Hashad, and this by identifying the historical stations of this idea and its most important developments at the level of the working class and its Maghreb trade union organizations In addition, the study highlights the extent of Farhat Hashad's contribution to this project through his relentless activity to carry out this project, in addition to identifying the various problems and difficulties encountered in this area, including World Trade Union University attempts to derail the union project, in addition to the aftermath of Farhat's assassination. A crowd for the Maghreb union project